Forming Family Welfare Villages: Efforts to Prevent Early Marriage in Denai Sarang Burung Village, Deli Serdang Regency - Siregar, Hairani; Nasution, Eva Syahfitri; Siregar, Rodiatul Hasanah; Dalimunthe, Ritha F; Ramadani; Siregar, Muhammad Bangun (Talenta Publisher, 2023)
This service activity was carried out in Denai Sarang Burung Village, Pantai Labu District, Deli Serdang Regency, North Sumatra Province, which has the challenge of early marriage as a serious social problem. Early marriage, which occurs when couples have not met the standards and age limits for married life, can have a negative impact on the local community. Therefore, prevention efforts involving families and adolescents are needed. Prevention activities are conducted through activities that aim to build communication between parents and teenagers. This includes training on making flower bouquet, snack bouquet and money bouquet. In addition, knowledge transfer was conducted on marriage law, the dangers of teenage promiscuity, and teenage reproductive health. The outcomes of this community service activity include the publication of scientific articles to be published in national journals, publication through mass media, and the making of videos to be uploaded on the YouTube platform. This activity was carried out in Denai Sarang Burung Village, Deli Serdang Regency, using FGD, counseling, and mentoring methods, involving synergy between local partners and the academic community of the University of North Sumatra.